2010
DOI: 10.1590/s0103-50532010000800012
|View full text |Cite
|
Sign up to set email alerts
|

pH effect in aquatic fulvic acid from a Brazilian river

Abstract: Estudos do comportamento morfológico dos ácidos fúlvicos foram realizados utilizando a técnica de microscopia de força atômica aliada às técnicas de potencial zeta e espectroscopia de fluorescência. Os resultados mostraram que o ácido fúlvico (AFA) de um rio tropical mudou a sua morfologia quando variado o pH da solução aquosa dos AFA. Em pH ácido a morfologia é mais granular formando aglomerados de altura entre 10-55 nm. Em pH alcalino os valores foram de 2,5-4,0 nm, sendo que a morfologia em condições alcali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 22 publications
3
5
0
Order By: Relevance
“…These results corroborate with Saab et al 28 and Zara et al 12 which suggested that in acid pH weak electrostatic interactions and hydrogen bonding are responsible for aggregates formation while in alkaline pH electrostatic interactions are strong due to the increase in groups ionization, resulting in more flexibles structures by dispersive forces.…”
Section: Sem Imagessupporting
confidence: 90%
“…These results corroborate with Saab et al 28 and Zara et al 12 which suggested that in acid pH weak electrostatic interactions and hydrogen bonding are responsible for aggregates formation while in alkaline pH electrostatic interactions are strong due to the increase in groups ionization, resulting in more flexibles structures by dispersive forces.…”
Section: Sem Imagessupporting
confidence: 90%
“…52 Under the experimental conditions used here (i.e., acidic pH), the phenolic groups are protonized and may form H-bonds with the deprotonized carboxylic groups. 58 For this reason, we suggest that the Hbonds play a more important role in SRFA aggregates stabilization as compared to that in PPFA.…”
Section: = −mentioning
confidence: 86%
“…Therefore, removal of Huma-K at pH 4 may be attributed to sorption as well as surface-induced and homogeneous precipitation. Similar results have been reported in studies of aquatic fulvic acid: at pH 3, fulvic molecules formed agglomerates at the surface of a mica sheet because most of the fulvic molecules were uncharged (Saab et al, 2010). Balnois et al (1999) studied the agglomeration of a hydrophilic humic acid from the Suwannee River and a peat humic acid on a surface of muscovite mica.…”
supporting
confidence: 76%